2020
DOI: 10.1073/pnas.2000950117
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing erectile dysfunction drugs tadalafil and vardenafil to increase bone mass

Abstract: We report that two widely-used drugs for erectile dysfunction, tadalafil and vardenafil, trigger bone gain in mice through a combination of anabolic and antiresorptive actions on the skeleton. Both drugs were found to enhance osteoblastic bone formation in vivo using a unique gene footprint and to inhibit osteoclast formation. The target enzyme, phosphodiesterase 5A (PDE5A), was found to be expressed in mouse and human bone as well as in specific brain regions, namely the locus coeruleus, raphe pallidus, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…Among 11 known PDE families, PDE5A, 6, and 9A are known to specifically bind to and degrade cGMP. Taqman assays using mRNA from mouse skeletal tissue evaluating the expression of 11 PDEs showed high levels of Pde5a expression, which was comparable to the expression of receptor activator of nuclear factor κB (RANK) ( Tnfrsf11a ) and RANKL ( Tnfsf11 ) 15 . Immunohistochemistry confirmed the colocalization of RUNX2 and PDE5A in osteoblast precursors; however, PDE5A was not stained in osteoclast precursors.…”
Section: Phosphodiesterase 5 and Bonementioning
confidence: 80%
See 4 more Smart Citations
“…Among 11 known PDE families, PDE5A, 6, and 9A are known to specifically bind to and degrade cGMP. Taqman assays using mRNA from mouse skeletal tissue evaluating the expression of 11 PDEs showed high levels of Pde5a expression, which was comparable to the expression of receptor activator of nuclear factor κB (RANK) ( Tnfrsf11a ) and RANKL ( Tnfsf11 ) 15 . Immunohistochemistry confirmed the colocalization of RUNX2 and PDE5A in osteoblast precursors; however, PDE5A was not stained in osteoclast precursors.…”
Section: Phosphodiesterase 5 and Bonementioning
confidence: 80%
“…In vivo studies showed protective skeletal effects of PDE5A inhibition, which are summarized in Table 1. In wild‐type mice, tadalafil and vardenafil significantly increased areal and volumetric BMD, including better microarchitecture, compared with vehicle‐treated mice 15 . Tadalafil and vardenafil increased serum NO, cGMP, and PKG expression, as well as BMD, in ovariectomized rats 59 .…”
Section: Phosphodiesterase 5 and Bonementioning
confidence: 92%
See 3 more Smart Citations